2012
DOI: 10.1016/j.ijpe.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The space of solution alternatives in the optimal lotsizing problem for general assembly systems applying MRP theory

Abstract: MRP Theory combines the use of Input-Output Analysis and Laplace transforms, enabling the development of a theoretical background for multi-level, multi-stage production-inventory systems together with their economic evaluation, in particular applying the Net Present Value principle (NPV). less thanbrgreater than less thanbrgreater thanIn a recent paper (Grubbstrom et al., 2010), a general method for solving the dynamic lotsizing problem for a general assembly system was presented. It was shown there that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…(70,309,075$) is minimum damages that has arisen in this project. Which shows the great importance of delay in receiving the goods [20][21][22][23]. Since delay value of goods may be overlapped in analyzing damages, means that simultaneous delay of two or more goods to the same extent causes damages, so in this analysis, the largest time delay is intended as a determinant factor of minimal damage and based on…”
Section: Dailymentioning
confidence: 99%
“…(70,309,075$) is minimum damages that has arisen in this project. Which shows the great importance of delay in receiving the goods [20][21][22][23]. Since delay value of goods may be overlapped in analyzing damages, means that simultaneous delay of two or more goods to the same extent causes damages, so in this analysis, the largest time delay is intended as a determinant factor of minimal damage and based on…”
Section: Dailymentioning
confidence: 99%
“…It is shown that in order for available inventory to be kept at finite levels at any time, the L4L solution must be valid for the time averages of production and demand, irrespective of the policy followed. Recently, [Grubbström et al, 2009, Grubbström andTang, 2012] it has been shown that the L4L solution determines all possible times when internal demand events can occur, so we may regard the currently considered property of the L4L solution as its third rôle.…”
Section: Introductionmentioning
confidence: 99%
“…This binary view led to the "inner-corner" condition for a production plan to qualify as a candidate for optimality, and it holds even for complex multi-item production structures (Grubbström, Bogataj andBogataj 2009, Grubbström andTang 2012). The inner-corner condition is a geometrical statement, in the discrete time case equivalent with "Inventory is not to be carried into a period where production takes place" (Aryanezhad 1992, pp.…”
mentioning
confidence: 99%
“…Curve B (dotted) illustrates the most general case of feasible production (any non-decreasing curve above or possibly touching cumulative demand), Curve C (dotted and dashed) the general case of feasible production taking place in batches, making cumulative production a staircase function, and Curve D (dashed) a batchproduction case which candidates for optimality, since it meets the inner-corner condition. (Grubbström and Tang 2012).…”
mentioning
confidence: 99%